2021
DOI: 10.1007/s42985-021-00102-x
|View full text |Cite
|
Sign up to set email alerts
|

Solving high-dimensional Hamilton–Jacobi–Bellman PDEs using neural networks: perspectives from the theory of controlled diffusions and measures on path space

Abstract: Optimal control of diffusion processes is intimately connected to the problem of solving certain Hamilton–Jacobi–Bellman equations. Building on recent machine learning inspired approaches towards high-dimensional PDEs, we investigate the potential of iterative diffusion optimisation techniques, in particular considering applications in importance sampling and rare event simulation, and focusing on problems without diffusion control, with linearly controlled drift and running costs that depend quadratically on … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
47
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(47 citation statements)
references
References 91 publications
(178 reference statements)
0
47
0
Order By: Relevance
“…It turns out, however, that the underlying nonlinear control problem belongs to a class of so-called linearly-solvable stochastic control problems that have been studied by Dvijotham and Todorov (2012), Schütte et al (2012) and others and that can be solved by other means (cf. also Nüsken and Richter (2020)). The corresponding theory goes back to Fleming and co-workers, and we mention only the seminal article Fleming (1977).…”
Section: Computing the Value Function: Hitting Probabilitiesmentioning
confidence: 87%
“…It turns out, however, that the underlying nonlinear control problem belongs to a class of so-called linearly-solvable stochastic control problems that have been studied by Dvijotham and Todorov (2012), Schütte et al (2012) and others and that can be solved by other means (cf. also Nüsken and Richter (2020)). The corresponding theory goes back to Fleming and co-workers, and we mention only the seminal article Fleming (1977).…”
Section: Computing the Value Function: Hitting Probabilitiesmentioning
confidence: 87%
“…In this work, we introduced a novel methodological framework for identifying optimal dynamical interventions for constraining diffusive systems. Distinctively from previous work [26,27,44,78] that devises optimal control protocols by employing iterative optimisation procedures, here, we obtained the required interventions in a deterministic and noniterative way. In particular, we showed that splitting the time-resolved constraining information into retrospective and prospective parts, allows for a representation of the optimal interventions in terms of the difference of logarithmic gradients (scores) of two forward probability flows.…”
Section: Discussionmentioning
confidence: 99%
“…We note in passing that Proposition 3.3 extends straightforwardly to L t,v diffusion,int under the assumption that v satisfies appropriate Lipschitz and growth conditions. Similar considerations apply for the BSDE loss, noting that for solutions to the generalized BSDE system [60]…”
Section: Forward Controlmentioning
confidence: 97%
“…refers to an appropriate function class, usually consisting of deep neural networks. With a loss function at hand we can apply gradient-descent type algorithms to minimize (estimator versions of) L, keeping in mind that different choices of losses lead to different statistical and computational properties and therefore potentially to different convergence speeds and robustness behaviours [60].…”
Section: Variational Formulations Of Boundary Value Problemsmentioning
confidence: 99%
See 1 more Smart Citation